POTENSI NIRA AREN (Arenga pinnata) SEBAGAI BAHAN BAKU BIOETANOL - Cahyana, Budi Tri; Wahyudi, Tejo (Jurnal Riset Industri Hasil Hutan, 2012)
Aren (Arenga pinnata) is one of the plants that can be utilize as the raw material for bioetanol. The research of bioetanol producing used nira aren as raw material has been conducted by yeast of pure culture Saccharomyces cerevisiae and fermipan. The process is done by fermentation and distillation based on the duration of fermentation, concentration ratio of starter to the substrate by each type of yeast used. The result of research shows that the highest yield of bioetanol on pure culture fermentation as long 50 hours with 10 % concentration of starter, that is 14,9 %. The highest content of bioetanol is on  fermentation as long 75 hours with 5 % concentration of starter, that is 73,0 %. Fermentation with fermipan, the the highest yield and concentration of bioetanol  is at the fermentation as long 75 hours with the starter concentration of 15 %, that is                  10,1 % and 66,0 %.Keywords:  nira aren, saccharomyces cerevisiae, fermipan, starter concentration, output concentration of bioetanol